The Implementation of Question and Answer Method in Teaching Speaking Skill at Eight Grade of UPTD SMP Negeri 9 Pematang Siantar - Silvia Torong; Widya Ambarita; Nikerian W. Manik (Journal Corner of Education, Linguistics, and Literature, 2023)
The research purpose is to find out the usage of implementation of Question and Answer method in teaching speaking skill to students. The population of the research is students of SMP Negeri 9 Pematang Siantar, with sample of a class consists of 31 students. This research applies quantitative method to collect data for the research. Researchers give oral test to the students and make their scores, then calculate the mean to create conclusion of this research. Based on research results, researchers found that 19 students were able to achieve the score of 65 and beyond, while 12 students were unable to achieve the minimum score (below 65). Therefore, 61% of students have sufficient speaking skills, meanwhile 39% students have weak speaking skills. Question and Answer method is a suitable method that can be utilized by the teachers in teaching English skills to students, especially to teach speaking skill.